Social studies for secondary schools : teaching to learn, learning to teach - Alan J. Singer (New York : Routledge, 2015)
Now in its 4th edition, this popular text for secondary social studies methods courses integrates discussions of educational goals and the nature of history and social studies with ideas for organizing social studies curricula, units, lessons, projects, and activities. A major theme throughout is that what teachers choose to teach and the way they teach reflect their broader understanding of society, history, and the purpose of social studies education. Advocating an inquiry and activity-based view of social studies teaching that respects the points of view of students and teachers, and based.
Includes bibliographical references and index.
Keywords: Social sciences -- Study and teaching (Secondary) -- United States; SOCIAL SCIENCE -- Essays; SOCIAL SCIENCE -- Reference